2015
DOI: 10.3390/lubricants3010027
|View full text |Cite
|
Sign up to set email alerts
|

On the Characteristics of Misaligned Journal Bearings

Abstract: Journal bearing misalignment arise generally from the shaft deformation under load, deflection of the shaft, manufacturing and assembly errors, improper installation, and asymmetric loading. During operations, misalignment has a considerable effect on the static and dynamic performances. It could cause wear, vibration and even system failure. In this article, a literature review of misalignment of the journal bearings is presented. The basic theory for the misalignment and some results for the circular journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 110 publications
0
32
0
1
Order By: Relevance
“…Misalignment results an increase in the wear rate and vibration levels thereby causing a reduction in the performance and life of a journal bearing. 21,22 Schematic diagram of journal bearings under normal and misaligned operating conditions is depicted in Figure 1. The details of the geometry of a journal bearing presented as shown in Figure 1(a) and (b) shows the hydrodynamic journal bearing in misaligned position, where the journal of the bearing has declined along the axial direction due to misalignment.…”
Section: Tribological Parameters To Assess the Performance Of Journalmentioning
confidence: 99%
“…Misalignment results an increase in the wear rate and vibration levels thereby causing a reduction in the performance and life of a journal bearing. 21,22 Schematic diagram of journal bearings under normal and misaligned operating conditions is depicted in Figure 1. The details of the geometry of a journal bearing presented as shown in Figure 1(a) and (b) shows the hydrodynamic journal bearing in misaligned position, where the journal of the bearing has declined along the axial direction due to misalignment.…”
Section: Tribological Parameters To Assess the Performance Of Journalmentioning
confidence: 99%
“…The use of additional oil in the bearings decreases the friction coefficient, especially at high velocities and pressures. 39,40 Kasai et al 38 enhanced the bearing performance increasing the lubricant pressure inside the bearing. In addition, it has been observed that the friction coefficient decreases using additional additives in lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common causes of wear in the bearing is misalignment between the shaft and the outer ring. The wear effect of misalignment occurs when [1]: asymmetric load is applied; the shaft or the outer ring are distorted; defaults of clearance appears after manufacturing.…”
Section: Introductionmentioning
confidence: 99%